UPAYA PENGELOLA ASRAMA DALAM MEMOTIVASI BELAJAR SISWA KELAS VI MADRASAH IBTIDAIYAH MAHAD AL-ZAYTUN - Nur Laila Al Hafidz; Moch. Hasyim Fanirin; Dede Indra Setiabudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Madrasah Ibtidaiyah is a basic educational institution that has an important role in shaping the quality of student learning. Education in the Ma'had Al-Zaytun environment is equipped with a boarding system, so that the dormitory manager has a big responsibility in guiding, educating, and motivating students to have high learning motivation. in this study is how the dormitory manager's efforts in motivating sixth grade students of Madrasah Ibtidaiyah Ma'had Al-Zaytun to learn, as well as what are the supporting and inhibiting factors in its implementation. The aim is to determine the efforts of dormitory managers in increasing student learning motivation and identifying the supporting and inhibiting factors faced. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research subjects involved dormitory managers, homeroom teachers, room teachers, and sixth grade students of Madrasah Ibtidaiyah Ma'had Al-Zaytun. Main problem The results of the study indicate that the dormitory manager's efforts in motivating student learning are by extending students' sleep hours, making the dormitory environment a comfortable and less conflict-prone place, conducting coaching and evaluation together with room teachers, and controlling student activities 24 hours a day through the WhatsApp application. Supporting factors include adequate facilities and infrastructure, a structured dormitory program, and collaboration between dormitory administrators in awarding prizes. Inhibiting factors include student laziness, negative peer influence, emotional issues, and a lack of interest in specific subjects. Thus, dormitory administrators have been shown to make a significant contribution to motivating students to learn, although challenges remain.